2016
DOI: 10.1007/s00018-016-2339-2
|View full text |Cite
|
Sign up to set email alerts
|

Selenoproteins and oxidative stress-induced inflammatory tumorigenesis in the gut

Abstract: Selenium is an essential micronutrient that is incorporated into at least 25 selenoproteins encoded by the human genome, many of which serve antioxidant functions. Because patients with inflammatory bowel disease (IBD) demonstrate nutritional deficiencies and are at increased risk for colon cancer due to heightened inflammation and oxidative stress, selenoprotein dysfunction may contribute to disease progression. Over the years, numerous studies have analyzed the effects of selenoprotein loss and shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 88 publications
2
49
0
Order By: Relevance
“…SEPP1 is a secreted glycoprotein with important immunomodulatory and antioxidant effects in the intestine [24][25][26] . Representative immunohistochemistry images of SEPP1 show qualitative changes consistent with our scRNA-seq analysis (Figure 5b).…”
Section: Regional Reprogramming Of Distal Si After Sbr Is Accompaniedmentioning
confidence: 99%
See 1 more Smart Citation
“…SEPP1 is a secreted glycoprotein with important immunomodulatory and antioxidant effects in the intestine [24][25][26] . Representative immunohistochemistry images of SEPP1 show qualitative changes consistent with our scRNA-seq analysis (Figure 5b).…”
Section: Regional Reprogramming Of Distal Si After Sbr Is Accompaniedmentioning
confidence: 99%
“…Quantification of this immunostaining via immunofluorescence demonstrated significant increases in SEPP1 (1.4 fold relative fluorescent intensity, p<0.05) in SBR relative to sham (Figure 5c). Furthermore, SEPP1 has been shown to suppress inflammation-associated tumorigenesis, in part through its effects on macrophage polarization, more specifically, by suppressing M2 associated Ym1 expression 25,27 . Interestingly, this is consistent with RNA-sequencing analysis we performed on sub-epithelial tissue from sham and SBR mice, showing that Ym1 is the second most depleted transcript in SBR mice (-6.19 fold depleted, p <0.05, unpublished).…”
Section: Regional Reprogramming Of Distal Si After Sbr Is Accompaniedmentioning
confidence: 99%
“…We believe that a larger cohort may provide more statistically significant findings. Notably, CD5L, EIF5A1, FINC, and SEPP1 particularly attracted our attention as, according to the literature, they are associated with tumorigenesis [51, 83-85]. In the present study, heat-resistant fractions of these proteins were identified in pancreatic cancer plasma, but not in normal plasma, and formed only after eDNA treatment, suggesting a role of this conversion in tumorigenesis.…”
Section: Discussionmentioning
confidence: 46%
“…Calcium-magnesium-dependent ATPase activity decreased in the heart and cortex regions of the animals that received selenium alone or combined, probably as a consequence of the changes in the enzyme affinity [27]. This effect may probably be because cellular calcium signaling is subjected to thiol-redox regulation by the selenoproteins [28] [29]. These results could be related with the reports of Naziroglu et al [30], who suggested that selenium increases the activity of Ca 2+ -ATPase thus, producing protective effect on the substances that increase brain lesions, by the inhibition of free radical production and regulation of calcium-dependent processes, as well as supporting the redox antioxidant system.…”
Section: Discussionmentioning
confidence: 99%